Dosimetry of local failure with single dose 19 Gy high-dose-rate brachytherapy for prostate cancer. (April 2021) - Armstrong, Shreya; Tsang, Yatman; Lowe, Gerry; Tharmalingam, Hannah; Alonzi, Roberto; Ostler, Peter; Hughes, Robert; Hoskin, Peter
Highlights: Of 180 patients who received 19 Gy high-dose-rate brachytherapy (HDR-BT) for localised prostate cancer, with a median follow up of 36 months, 19 (10.6%) patients developed biochemical recurrence of which 13 had a local relapse, including 7 at the site of dominant intraprostatic nodule (DIL). The 19 biochemical recurrences (failures) were matched to 19 control patients, who were matched to pre-treatment CTV size, Gleason score, T stage, risk category and presence of a DIL. For these patients, clinical and dosimetric parameters were analysed to see if there were any predictors for biochemical recurrence, local recurrence or recurrence within the DIL. There were no statistically significant differences in all OARs, CTV, PTV and DIL dosimetric parameters between the failures and controls. In univariate analysis, there were no statistically significant clinical or dosimetric parameters that predicted for biochemical progression free survival, local recurrence free survival or DIL recurrence free survival. Whilst a large proportion of patients recur at the site of original disease, and these results may support rationale for further dose escalation, in our cohort actual dose delivered to DIL was around 26 Gy. Other studies employing dose escalation to whole gland or focal boost have failed to show improved clinical outcomes to justify this approach, hence HDR-BT should be undertaken using a minimum of two fractions. Abstract: Purpose/objective: Long-term follow up of single dose high-dose rate brachytherapy (HDR BT) for localised prostate cancer has revealed higher than expected rates of biochemical and local failure. This study aimed (i) to investigate the pattern of relapse within the prostate with reference to the initial site of disease in those patients; and (ii) to examine if there were any relationships between the HDR BT dosimetric parameters to these areas of recurrence. Materials/methods: A retrospective review of treatment records of patients who received 19 Gy single fraction of HDR BT was carried out. A matched pair analysis used one control for each biochemical recurrence case matched with pre-treatment Clinical target volume (CTV) size, Gleason score, T stage, risk category and presence of an identifiable dominant intraprostatic nodule (DIL) for each biochemical recurrence case identified. For all datasets, the pre HDR BT DILs were delineated on the diagnostic pre-treatment T2-weighted MRI and planning CT images. For patients with local recurrence post HDR BT, the recurrent nodules were contoured on the diagnostic T2-weighted MRI and choline PET which were registered to the original HDR BT planning CT. Dosimetric parameters of CTV, planning target volume (PTV), DIL and organs at risk (OARs) were evaluated. Wilcoxon signed-rank test was performed to investigate if there were any significant differences in dosimetric parameters between cases and controls. Cox regression analysis was performed to explore if there were any clinical and dosimetric parameters predicting for biochemical progression free survival (bPFS), local recurrence free survival (LR-PFS) and DIL recurrence free survival (DIL-PFS). Results: Between 2013 and 2018, 180 patients received 19 Gy HDR-BT monotherapy. With a median follow up of 36 months, 19 (10.6%) patients developed biochemical recurrence. Of the 19 patients with biochemical failure, 13 had a local recurrence, including 7 who occurred at the site of DIL. Thirty-eight intermediate/high risk patients were included in the matched pair analysis. No statistically significant differences were found in all CTV, PTV, DIL and OAR dosimetric parameters between cases and controls ( p  > 0.05). For the Cox regression analysis, none of the covariates investigated were found to be statistically significant factors to predict for bPFS, LC-PFS and DIL-PFS. Conclusion: No associations between biochemical recurrences and HDR BT dosimetry were identified in our cohort of patients receiving 19 Gy single fraction HDR BT. A large proportion of recurrences occurred at the site of original disease. HDR BT for intermediate/high risk prostate cancer should be undertaken using a minimum of two fractions.